BULLYING PREVENTION IN JUNIOR HIGH SCHOOLS: A QUALITATIVE STUDY OF PERMENDIKBUDRISTEK NO. 46/2023 IMPLEMENTATION IN KARAWANG WITH ISLAMIC PERSPECTIVES - Oyoh Bariah; Rina Marlina; Iwan Hermawan; Nur Aini Farida (Academic Bright Collaboration, 2026)
This study examines the implementation of Permendikbudristek No. 46 of 2023, Indonesia's bullying prevention policy, in junior high schools in Karawang Regency, where empirical evidence on policy translation at the regency level remains limited. A descriptive-qualitative approach was used. Data were collected through semi-structured interviews with school stakeholders (principals, counselors, teachers) and document analysis from three pilot junior high schools in West Java. Thematic analysis was applied inductively. The findings show that bullying prevention is implemented through five integrated strategies: (1) character education embedded in daily routines, (2) establishment of school supervisory teams, (3) teacher capacity building, (4) parental socialization sessions, and (5) school-based awareness campaigns using posters, social media, and educational videos. Character reinforcement is further operationalized through Pancasila Student Profile (P5) projects and routine spiritual, literacy, and numeracy activities. While all three schools implemented the policy, variation was observed: one school demonstrated high consistency across all five strategies, whereas two schools showed partial implementation due to limited teacher training and irregular parental engagement. Nevertheless, all schools reported increased stakeholder awareness (approximately 70–85% of teachers and staff reported improved understanding of bullying indicators) and improved preventive practices, including a 40–50% reduction in reported minor bullying incidents over a six-month period. The study’s reliance on self-reported stakeholder perceptions and document analysis may introduce social desirability bias. The small sample of three schools in one regency limit the generalizability of findings to other regions with different sociocultural or institutional conditions. Additionally, the cross-sectional design captures implementation at a single point in time, precluding conclusions about long-term policy sustainability. Future research should include longitudinal designs and observational methods to validate behavioral changes. This is among the first empirical studies of Permendikbudristek No. 46 in a regency context, offering practical insights for district education authorities and schools implementing national anti-bullying policies.